2022
DOI: 10.1097/mbp.0000000000000629
|View full text |Cite
|
Sign up to set email alerts
|

Conventional office blood pressure measurements and unattended automated office blood pressure compared with home self-measurement and 24-h ambulatory blood pressure monitoring

Abstract: Objective To assess whether automated office blood pressure (BP) (AOBP) measurement is a better method for measuring BP in the office than conventional techniques and an alternative to out-of-office BP measurements: home-self BP (HSBP) or ambulatory BP monitoring (ABPM). Methods We conducted a cross-sectional study of 74 patients and compared AOBP with the conventional technique using a mercury sphygmomanometer and with both out-to-office BP measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Previous studies reported different results between ausAOBP and other office BP measurements, aAOBP and aUAOBP, 13 14 15 16 and recent meta-analyses also showed inconsistent results. 8 9 10 However, because most of these studies were conducted in hypertensive patients, 13 14 15 they may not be representative of the BP in non-hypertensive and hypertensive individuals in general practice.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies reported different results between ausAOBP and other office BP measurements, aAOBP and aUAOBP, 13 14 15 16 and recent meta-analyses also showed inconsistent results. 8 9 10 However, because most of these studies were conducted in hypertensive patients, 13 14 15 they may not be representative of the BP in non-hypertensive and hypertensive individuals in general practice.…”
Section: Discussionmentioning
confidence: 91%
“…Many studies have compared the discrepancies between office BP and out-of-office BP measurements. 7 8 9 11 12 13 14 15 16 17 However, only a few studies have included four or five methods of measuring BP, as we did. 16 18 19 20 The results differed between studies with differences in the study population.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation